A Note on Frame Distributions - Kock, Anders; Reyes, Gonzalo E. (BRICS Report Series, 1997)
In the context of constructive locale or frame theory (locale theory over a fixed base locale), we study some aspects of 'frame distributions', meaning sup preserving maps from a frame to the base frame. We derive a relationship between results of Jibladze-Johnstone and Bunge-Funk, and also descriptions in distribution terms, as well as in double negation terms, of the 'interior of closure' operator on open parts of a locale.